2000
DOI: 10.1128/aem.66.7.2981-2987.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the Malic Enzyme Gene from Corynebacterium glutamicum and Role of the Enzyme in Lactate Metabolism

Abstract: Malic enzyme is one of at least five enzymes, known to be present in Corynebacterium glutamicum, capable of carboxylation and decarboxylation reactions coupling glycolysis and the tricarboxylic acid cycle. To date, no information is available concerning the physiological role of the malic enzyme in this bacterium. The malE gene from C. glutamicum has been cloned and sequenced. The protein encoded by this gene has been purified to homogeneity, and the biochemical properties have been established. Biochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 55 publications
3
69
1
Order By: Relevance
“…Both pathways require 4 mol NADPH per mol lysine starting from oxaloacetate. In principle, NADPH can be synthesized in C. glutamicum by the enzymes of the oxidative pentose phosphate pathway (PPP), glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase (Moritz et al 2000), by isocitrate dehydrogenase (Eikmanns et al 1995) and by malic enzyme (Gourdon et al 2000). Carbon flux analysis revealed that during growth on glucose, NADPH for lysine biosynthesis is provided by the PPP, whereas isocitrate dehydrogenase and malic enzyme are of minor importance (Marx et al 1996(Marx et al , 1997(Marx et al , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Both pathways require 4 mol NADPH per mol lysine starting from oxaloacetate. In principle, NADPH can be synthesized in C. glutamicum by the enzymes of the oxidative pentose phosphate pathway (PPP), glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase (Moritz et al 2000), by isocitrate dehydrogenase (Eikmanns et al 1995) and by malic enzyme (Gourdon et al 2000). Carbon flux analysis revealed that during growth on glucose, NADPH for lysine biosynthesis is provided by the PPP, whereas isocitrate dehydrogenase and malic enzyme are of minor importance (Marx et al 1996(Marx et al , 1997(Marx et al , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we determined that dinucleotides inhibited the reaction. When either 0.50 mM NAD þ or 0.50 mM NADH was added, the specific activity was reduced by approximately 50% ( [6]. However, no signal could be detected.…”
Section: Biochemical Characterizationmentioning
confidence: 99%
“…The prokaryotic MEs described so far are fewer in number and more diverse in structure than their eukaryotic counterparts. MEs have been characterized from Bacillus stearothermophilus [2], Sulfolobus solfataricus [3], Rhizobium meliloti [4,5], Corynebacterium glutamicum [6] and Streptococcus bovis [7].…”
Section: Introductionmentioning
confidence: 99%
“…For malic enzyme no clear effects could be observed so far. Neither deletion nor overexpression of the corresponding gene influenced the metabolism of C. glutamicum on sugars markedly [21,152].…”
Section: Metabolic Engineering Of Precursor Supplymentioning
confidence: 93%
“…For anaplerotic replenishment of the TCA cycle, C. glutamicum exhibits pyruvate carboxylase [20] and phosphoenolpyruvate (PEP) carboxylase as carboxylating enzymes. Malic enzyme [21] and PEP carboxykinase [22,23] catalyze decarboxylation reactions from the TCA cycle towards glycolysis. As additional gluconeogenetic enzymes, oxaloacetate decarboxylase [24] and PEP synthetase [25] have been proposed.…”
Section: Central Carbon Metabolismmentioning
confidence: 99%